The Impact of Agricultural Credit on Planting Structure: An Empirical Test of Factor Allocation - Huishuang Jin; Hui Liu (Land)
Rural finance provides financial support for agricultural production. Agricultural credit, as the most important rural financial resource, is designed to regulate rural economic activity and guide the rational adjustment of the rural economy and industrial structure. However, the relationship between the availability of credit to farmers and their choice of cropping behavior in the agricultural production process remains unexplored in depth. To fill this gap, this study constructs an analytical framework for ‘Agricultural credit-production factor allocation-planting structure decision-making behaviour’. Using data from a large-scale rural survey in China, this paper empirically examines the impact of agricultural credit on the specialization and ‘grain-oriented’ of farm households’ planting structure using the OLS model, the mediated effects model, and the 2SLS model. In addition, this study explores the mechanism of the allocation of agricultural production factors in this process. This has enriched the theoretical and practical research on rural finance for agricultural development. Studies have shown that agricultural credit contributes significantly to the specialization and ‘grain-oriented’ of the planting structure. The findings of the study also show that agricultural credit promotes cropping restructuring among farmers through large-scale operations, technological advancement, and green production. In addition, there are differences in the impact of agricultural credit on the planting structure depending on the type of food-producing area, the scale of operation, the development of digital infrastructure, the education of the head, and the source of credit. These findings suggest that increasing rural financial support and promoting the restructuring of land improvement, agricultural machinery, and green production factors may be an effective path to optimizing the cropping structure and improving the efficiency of production factor utilization.